2019
DOI: 10.1101/614602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultraviolet light degrades the mechanical and structural properties of human stratum corneum

Abstract: Prolonged exposure of human skin to sunlight causes photodamage, which induces the early onset of wrinkles and increased tissue fragility. While solar ultraviolet (UV) light is considered to have the most damaging effect, the UV range that is most harmful remains a topic of significant debate. In this study, we take a first step towards elucidating biomechanical photoageing effects by quantifying how exposure to different UV ranges and dosages impacts the mechanical and structural properties of human stratum c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
1
14
0
1
Order By: Relevance
“…When an inhibitor of serine proteases was introduced, the moisture-dependent increase in tissue extensibility was prevented. Finally, the stiffness of the SC was largely unchanged even at high doses of UV radiation, while the fracture strength and fracture strain of the SC decreased with increasing UV exposure [74, 75], indicating that UV influences cellular cohesion, dominated by both intercellular lipids and CDs, while not interfering with the mechanical resistance of the tissue, which is mainly controlled by the keratin matrix and the rigid CE of corneocytes. A dispersion in the localization of DSG1 in the tissue, indicating degradation of CDs after UV radiation treatment, was also observed [75].…”
Section: Corneodesmosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…When an inhibitor of serine proteases was introduced, the moisture-dependent increase in tissue extensibility was prevented. Finally, the stiffness of the SC was largely unchanged even at high doses of UV radiation, while the fracture strength and fracture strain of the SC decreased with increasing UV exposure [74, 75], indicating that UV influences cellular cohesion, dominated by both intercellular lipids and CDs, while not interfering with the mechanical resistance of the tissue, which is mainly controlled by the keratin matrix and the rigid CE of corneocytes. A dispersion in the localization of DSG1 in the tissue, indicating degradation of CDs after UV radiation treatment, was also observed [75].…”
Section: Corneodesmosomesmentioning
confidence: 99%
“…CDs seem to play a major role in the cohesion of SC, which can be divided into 2 main regions: the deeper-immature SC, which is much more cohesive, and the outer SC, for which flexibility and plasticity may depend on intercellular lipids and the honeycomb localization of CDs. It is important to note that the honeycomb structure of the outer SC seems to be preferred in most body regions, but not for the palmar and plantar zones [75, 76]. In these regions, there prevails a strong cohesion between corneocytes, with CDs dispersed on the whole surface.…”
Section: Corneodesmosomesmentioning
confidence: 99%
“…Previous studies demonstrated that high efficiency nitrate removal by photocatalytic reduction with low remaining [NH + 4 ] could be achieved by silver-(Ag-) doped TiO 2 nano-particles under high-performance light sources (i.e., highpressure Hg lamps and xenon lamps) [4][5][6]. However, those light sources have disadvantages that include high energy consumption, potential human health hazard, and generating high heat [7,8]. For those reasons, the UVA light bulb is chosen for this process because it overcomes those disadvantages and is powerful enough for this process [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Desmosomes are associated with maintaining tissue integrity and resisting mechanical forces, especially in those tissues that are exposed to intense mechanical stress. 15 Recent work demonstrates that ultraviolet light induced changes in the mechanical properties of human stratum corneum disrupt the presence and location of DSG1, 37 suggesting an important role of DSG1 in contributing to tissue stiffness. A previous study demonstrated that appropriate tissue hydration was a key factor contributing to optimal mechanical properties.…”
Section: Discussionmentioning
confidence: 99%